2016
DOI: 10.3390/ma9060491
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Evaluation of Polyetheretherketone (PEEK) as a Core Material and a Comparison with Gold Standard Core Materials

Abstract: This study investigated the colorimetric properties of different veneering materials on core materials. Standardized specimens (10 mm × 10 mm × 1.5 mm) reflecting four core (polyetheretherketone (PEEK), zirconia (ZrO2), cobalt–chromium–molybdenum alloy (CoCrMo), and titanium oxide (TiO2); thickness: 1.5 mm) and veneering materials (VITA Mark II, IPS e.max CAD, LAVA Ultimate and VITA Enamic, all in shade A3; thickness: 0.5, 1.0, 1.5 and 2 mm, respectively) were fabricated. Specimens were superimposed to assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…These findings were in accordance with Stawarczyk et al (17) who studied the spectrophotometric evaluation of PEEK as a core material and showed that CieLab-System and VITA EasyShade parameters showed a significant impact of core, veneering material, and thickness of the veneering material. Also, the results were coinciding with Zeighami et al (18) who revealed that the veneering thickness affected the color and translucency of PEEK restorations.…”
Section: Discussionsupporting
confidence: 91%
“…These findings were in accordance with Stawarczyk et al (17) who studied the spectrophotometric evaluation of PEEK as a core material and showed that CieLab-System and VITA EasyShade parameters showed a significant impact of core, veneering material, and thickness of the veneering material. Also, the results were coinciding with Zeighami et al (18) who revealed that the veneering thickness affected the color and translucency of PEEK restorations.…”
Section: Discussionsupporting
confidence: 91%
“…An in vitro study evaluated the colorimetric properties of different veneering materials on PEEK, zirconium oxide (ZrO 2) , cobalt-chromium-molybdenum alloy (CoCrMo), and titanium oxide. PEEK showed comparable results when compared to well established core materials such as ZrO 2 and CoCrMo with respect to the CieLab-System parameters of the assemblies and the modification of the CieLab-System parameters for each veneering material [72].…”
Section: Randomized Clinical Trialmentioning
confidence: 85%
“…PEEK is increasingly used in the manufacture of removable and fixed prostheses [ 96 ], such as dental crowns, bridges and denture clamps in removable dental prostheses [ 38 , 97 , 98 , 99 , 100 ]. This is due to its advantages, including low potential to deduce an allergy, low water solubility, superior biocompatibility, high thermal and chemical resistance, moderate biofilm formation and excellent mechanical properties [ 97 , 98 ].…”
Section: Effects Of Peek For Prosthodontics Applicationsmentioning
confidence: 99%
“…Crown restorations made from PEEK exhibit poor aesthetics when restoring anterior teeth. The greyish and opaque color has limited PEEK for crown restorations [ 29 , 31 , 96 , 111 ]. The PEEK framework combined with veneering could provide a satisfactory aesthetic outcome [ 12 ].…”
Section: Effects Of Peek For Prosthodontics Applicationsmentioning
confidence: 99%